1985
DOI: 10.33584/jnzg.1985.46.1720
|View full text |Cite
|
Sign up to set email alerts
|

Autumn Saved Pasture in a High Frost Environment

Abstract: Herbage mass, moisture content and in vitro OMD of autumn saved ryegrasslwhite clover pasture grown on irrigated flats in the Upper Waitaki Basin were monitored over four winters from 1979-82. During the winter of 1981 and 1982 the effect of closing date and nitrogen application was examined. In addition Merino ewes were all-grasswintered from mid June to mid September without supplements on a feed allowance of 1.2 kg DMlhd.day to determine effect on liveweight. Mean herbage mass and OMD loss from mid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
2
6
0
Order By: Relevance
“…Thus it is not surprising that white clover was most frequent on shady aspects (Figure 1). At Tara Hills grazing research relevant to high/shady landscapes as defined in this paper has shown management has little influence on white clover cover (Allan 1985). The data presented here supports this, and shows the same thesis applies to high/sunny and low/shady landscapes.…”
Section: Cloverssupporting
confidence: 75%
See 3 more Smart Citations
“…Thus it is not surprising that white clover was most frequent on shady aspects (Figure 1). At Tara Hills grazing research relevant to high/shady landscapes as defined in this paper has shown management has little influence on white clover cover (Allan 1985). The data presented here supports this, and shows the same thesis applies to high/sunny and low/shady landscapes.…”
Section: Cloverssupporting
confidence: 75%
“…Ryegrass seed is seldom included in high country oversowing seed mixes (Scales et al 1975) probably because the species is not successful under uncontrolled utilisation and is considered inferior in its ability to carry well into the winter. But recent evidence shows ryegrass quality does not deteriorate greatly when frosted (Daly & Allan 1985, Scott & Maunsell 1986, and the authors feel that if a good level of utilisation (eg 60-70%) is intended, then ryegrass must be included in the oversowing mix.…”
Section: Grassesmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a protective layer was not evident in the 1982 season when autumn ADM levels were much lower. Daly & Allan (1985) found herbage was desiccated during winter at Tara Hills (near the present study) in their study on autumn-saved pasture. A protective layer probably causes air to become drier underneath, dehydrates and lowers the freezing point of the green herbage, and reduces consequent frosting damage, in the manner described by Primault (1979).…”
Section: Discussionsupporting
confidence: 44%